A Socioeconomic Study of Climate Change and its Impact on the Livelihoods of People Living Around the Coastal Areas of the Gambia - Fanneh, Momodou Mustapha (Journal of Accounting, Business and Finance Research, 2021)
The research aims to assess the effects of climate change on the livelihoods of people living around the coastal areas and the coping strategies used. The study uses a quantitative method with a semi-structured interview questionnaire and convenient sampling method and conducts a survey of coastal community residents in Banjul, Barra, Bakau, Tanji, Sanyang, Gunjur, and Kartong using a descriptive analysis. The majority of respondents are self-employed as fishermen, fish dryers, fish smokers, ship builders and boat riders. Most of the borrowing is done individually, the line of credit is mostly below D20,000, and more than 85% receive less than that amount. More than 60% of the respondents have no access to land, and 4.71% stated that they do not have access to water. Most of the respondents rank their friends as their source of borrowing followed by families and banks. About 93% stated that it takes them less than 40 minutes to get to the nearest health facility. Adaptation strategies employed to deal with health problems during variable and extreme climate are going to hospital, cleanliness, eating healthily, and using herbal medicine. More than 85% of the respondents did not experience a shortage of food in the period of a year, but the price of food has been increasing over the last five years. Finally, the respondents’ preferred adaptation strategy is saving followed by getting involved in other livelihood activities, government assistance, cleaning the environment, tree planting, and protection of coastal areas.